Examining perception of competency through practicum competencies outline. Issue 8 (1st September 2015) - Esposito, Giovanna; Freda, Maria Francesca; Bosco, Valentina
Abstract : Purpose: – This study aims to examine the self-perceived competencies of 231 Italian students enrolled in a psychological degree program and involved in a practicum. It analyzes the subjective perception of the competences that students expect to develop, acknowledge as developed and that might be inferred from tasks performed during the practicum; the level of expertise (novice, intermediate or advanced) of these competences; and the relation between the practicum facility and the competences. Design/methodology/approach: – This study administered an ad hoc survey comprising open-ended questions and used the Practicum Competencies Outline (Hatcher and Lassiter, 2007) as a framework for the content analysis. Findings: – The results revealed poor perception of some competency domains, such as Diversity: Individual and Cultural Differences; Development of Leadership; Application of Research and Ethics; and a frequent acknowledgment of Psychological Assessment and Professional Development. Before the practicum, the students expected to develop competence mainly at a novice level of expertise; after the practicum, the intermediate level of competences acknowledged as developed and inferred from performed tasks increased. Research limitations/implications: – The findings have implications for research on competence-based training, such as the necessity of self-assessment training evaluation. Practical implications: – Undergraduate psychology students must reflect on the value of psychological competences during their formative training to re-orient their learning process and build a competent professional role. Moreover, psychological facilities and university must share common objectives in training undergraduate students. Originality/value: – This study is the first attempt to analyze Italian college students' subjective perceptions of psychological competencies expected or developed during practicum .